Kepala Sekolah Sebagai Pemimpin dan Supervisor - Muhammad Ali Hanafiah (Hikmah, 2018)
The principal is an educational leader who has a very big role in developing the quality of education in schools. The quality of leadership of the principal is very influential on the formation of morale, harmonious cooperation, interest in educational development, pleasant working atmosphere, and professional quality improvement among teachers. The principal as an Administrator is responsible for the smooth implementation of education and teaching in his school. This includes all school activities, such as; teaching-learning process, student affairs, personnel, infrastructure, administration and finance, and arranging school relationships with the community. In addition, the principal is responsible for the state of the school environment.The Principal as Supervisor is in charge of supervising the teachers and school staff so that each school can gradually progress and develop as a tool fully qualified to achieve the educational objectives.